RAK ACCESSORIES FUNNY - Wahyuni Oktavia; Zulfahita Zulfahita; Siwi Sukmawati D. N; Syahwan Syahwan; Yuniati Yuyun (STKIP Singkawang, 2020)
Student creativity program in this entrepreneurship class, we run a business program of making cute accessory shelves from used cardboard. This used cardboard is very easy to get at the nearest shops or buy and sell used goods and the price is also quite affordable. Besides being easy to get, used cardboard is also easy to make several forms of crafts, one of which is a shelf. The shelf that we are going to make is a small shelf model where this shelf is made in various shapes, which will make many people like these models. Here what we need in addition to tools and materials is that we need skills and strong creative power. So that the shelves that we will create can attract consumers to buy. In the community, there are many unique shelves that make consumers want to buy them, but the price is a little less affordable for consumers' wallets. Therefore we take advantage of this situation to make cute accessory racks in order to help consumers more comfortable arranging their accessories or makeup with hemp by using this cute accessory rack that we made. The form of our business is that it is still in an individual stage and indeed this business is still new and is still trying to enter the business world. But we already have our own business brand, namely